PENGARUH KOTAK PENGADUAN PERUNDUNGAN TERHADAP KASUS PERUNDUNGAN DI SD NEGERI 193 PEKANBARU - Susilawati Ningsih; Febrina Dafit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the influence of the bullying complaint box on reducing bullying cases at SD Negeri 193 Pekanbaru. The issue addressed is the ongoing physical and verbal bullying and the low reporting rate due to fear and the absence of safe reporting channels. Using a quantitative ex post facto design, data were collected from 192 students determined through Slovin’s formula. Two validated questionnaires Complaint Box Usage and Bullying Cases were used as instruments. Data analysis involved descriptive statistics, normality and linearity tests, and simple linear regression. Results show that students’ use of the complaint box is categorized as good, indicating that they understand its role as a safe reporting medium. The normality and linearity tests confirmed that the data met analytical assumptions. Regression results showed a significance value below 0.05, meaning the complaint box significantly affects bullying cases. The coefficient of determination (R² = 0.044) indicates that the complaint box contributes 4.4% to reducing bullying, while 95.6% is influenced by other factors. Overall, the findings show that the complaint box is an effective tool in helping reduce bullying at school.